PARTISIPASI MASYARAKAT DALAM PENATAAN LINKUNGAN HIDUP DI DUSUN V DESA MAMUNGAA TIMUR KECAMATAN BULAWA KABUPATEN BONE BOLANGO - Artit Dalangko; Darman; Siske Anani (Journal of Economic, Business, and Administration (JEBA), 2023)
This study aims to: (1) To determine the level of community participation in maintaining cleanliness in East Mamungaa Village. (2) To know what factors influence the community to participate in maintaining cleanliness in East Mamungaa Village. The current study used a descriptive research design. This research was located in East Mamungaa Village, specifically in hamlet five (V) Bulawa District, Bone Bolango Regency. The data has been collected using observation, interview, and documentation. The population was people in hamlet five (V) of East Mamungaa Village who participated in the interview on environmental arrangements. Moreover, the sampling of 15 people used a random sampling technique. The type of data used is qualitative including data presented in the form of verbal words which was not in the form of numbers, whose data source is obtained from the East Mamungaa Village Community, hamlet five (V). The data analysis technique used in this study is a qualitative method. Based on the results, it was obtained that the people of east Mamungaa Village already have awareness of how to participate in environmental arrangements, however, some communities still do not understand the importance of environmental arrangements because there are still many communities who are not supportive and prejudiced in new things.